Their double lives - Hendricks, Jaime Lynn (Scarlet, an imprint of Penzler Publishers, 2025)
"A down-on-her-luck waitress at a posh New Jersey country club, Kim Valva couldn't be living a more different life from the carefree socialites she serves. Her live-in boyfriend recently cheated on her, her social life is in shambles, and her dog needs a life-saving surgery that she can't afford. Then her luck seems to change when a mysterious figure identifying themself only as The Stranger contacts her with an offer she can't refuse: Put a pill in the new member's drink and, when he dies, she'll have enough money to fix her dog and her life. Kim's target turns out to be Tony Fiore--Kim's bad boy ex-boyfriend from high school. Fifteen years have passed, and he now goes by Anthony Fuller. He's cleaned up, made tens of millions, and his gorgeous fiancée, twenty-two-year-old PJ Walsh, is on his arm. Stunned to see Tony again, Kim can't bring herself to go through with spiking his drink. Instead, it is PJ who dies horrifically at the table just as dinner ends. Was someone else at the club--member or worker--tasked with poisoning PJ just as she had been instructed to do to Tony? Who would want both of them dead? With no one to trust and The Stranger to answer to, Kim must peel back the layers of deceit to reveal a deeply buried truth, more shocking than she could ever imagine..." --